Optimal voltage stimulation parameters for network-mediated responses in wild type and rd10 mouse retinal ganglion cells. (3rd February 2017) - Jalligampala, Archana; Sekhar, Sudarshan; Zrenner, Eberhart; Rathbun, Daniel L
Abstract: To further improve the quality of visual percepts elicited by microelectronic retinal prosthetics, substantial efforts have been made to understand how retinal neurons respond to electrical stimulation. It is generally assumed that a sufficiently strong stimulus will recruit most retinal neurons. However, recent evidence has shown that the responses of some retinal neurons decrease with excessively strong stimuli (a non-monotonic response function). Therefore, it is necessary to identify stimuli that can be used to activate the majority of retinal neurons even when such non-monotonic cells are part of the neuronal population. Taking these non-monotonic responses into consideration, we establish the optimal voltage stimulation parameters (amplitude, duration, and polarity) for epiretinal stimulation of network-mediated (indirect) ganglion cell responses. We recorded responses from 3958 mouse retinal ganglion cells (RGCs) in both healthy (wild type, WT) and a degenerating ( rd10 ) mouse model of retinitis pigmentosa—using flat-mounted retina on a microelectrode array. Rectangular monophasic voltage-controlled pulses were presented with varying voltage, duration, and polarity. We found that in 4–5 weeks old rd10 mice the RGC thresholds were comparable to those of WT. There was a marked response variability among mouse RGCs. To account for this variability, we interpolated the percentage of RGCs activated at each point in the voltage-polarity-duration stimulus space, thus identifying the optimal voltage-controlled pulse (−2.4 V, 0.88 ms). The identified optimal voltage pulse can activate at least 65% of potentially responsive RGCs in both mouse strains. Furthermore, this pulse is well within the range of stimuli demonstrated to be safe and effective for retinal implant patients. Such optimized stimuli and the underlying method used to identify them support a high yield of responsive RGCs and will serve as an effective guideline for future in vitro investigations of retinal electrostimulation by establishing standard stimuli for each unique experimental condition.